Radicalism and Reputation : The Career of Bronterre O'Brien - Turner, Michael J. (Book collections on Project MUSE., 2017)
"A thematic analysis of the career of Bronterre O'Brien, one of the most influential leaders of Chartism, this book relates his activities--and the Chartist movement--to broader themes in the history of Britain, Europe, and America during the nineteenth century. O'Brien (1804-64) came to be known as the "schoolmaster" of Chartism because of his efforts to describe and explain its intellectual foundations. The campaign for the People's Charter (with its promise of political democratization) was a highpoint in O'Brien's career as writer and orator, but he was already well known before the campaign began, and during the 1840s he distanced himself from other Chartist leaders and from several important Chartist initiatives. This book examines the personal, tactical, and ideological reasons for O'Brien's departure, as well as his development of a social and economic agenda to accompany "constitutional" Chartism, in line with the evolution of radical thought after the Great Reform Act of 1832. It also evaluates O'Brien's reputation, among his contemporaries and among modern historians, in order better to understand his contribution to radicalism in Britain and beyond"--